The effect of reading questioning answering integrated with creative problem solving on critical thinking - Naafi Aisya; I. Ibrohim; Susriyati Mahanal; Hidayati Maghfiroh (University of Muhammadiyah Malang, 2023)
Although the empowerment of critical thinking (CT) has become an international concern that needs to be developed in the biology learning process for high school students, there still needs to be more relevant research literature. This study aimed to compare the effectiveness of implementing reading, questioning, and answering strategies integrated with creative problem solving (RQA-CPS) with RQA, CPS, and discussion strategies. This method used the pretest-posttest non-equivalent control group design for one semester using four classes. We designed that the experimental group was taught with RQA-CPS, the control-I group was taught with RQA, the control-II group was taught with CPS, and the control-III group was taught with DP. This research involved 129 high school students in four classes with the topics Plantae, Animalia, Ecology and Environmental Change. These four topics are classified as complex material that requires CT to be able to understand in depth. The results showed that high school students' CT increased in all four classes, but the RQA-CPS group experienced the most significant increase and was significantly different compared to the other three control groups. Thus, the RQA-CPS strategy should be used in learning to improve students' CT.